2015
DOI: 10.3390/ijerph121214958
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Work: Validation of a New Instrument in Three Languages

Abstract: Introduction and objective: A new instrument to measure quality of work was developed in three languages (German, French and Luxembourgish) and validated in a study of employees working in Luxembourg. Methods and results: A representative sample (n = 1529) was taken and exploratory factor analysis revealed a six-factor solution for the 21-item instrument (satisfaction and respect, mobbing, mental strain at work, cooperation, communication and feedback, and appraisal). Reliability analysis showed satisfying rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…A review of job quality approaches has shown the need for a new questionnaire that covers the most recent conceptualization of job quality. Moreover, our aim was to connect the JD-R model that is well established in work psychology [ 42 , 43 , 44 , 45 , 46 , 47 ] with the job quality debate [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The proposed two job quality indices (i.e., QoW and QoE) contain job characteristics that are linked to well-being and/or health outcomes, and are rooted in the JD-R model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of job quality approaches has shown the need for a new questionnaire that covers the most recent conceptualization of job quality. Moreover, our aim was to connect the JD-R model that is well established in work psychology [ 42 , 43 , 44 , 45 , 46 , 47 ] with the job quality debate [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The proposed two job quality indices (i.e., QoW and QoE) contain job characteristics that are linked to well-being and/or health outcomes, and are rooted in the JD-R model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, job quality can be seen as a multidimensional and elusive concept [8]. Perhaps because of this inherent multidimensionality and elusiveness, there are multiple and relatively diffuse concepts that have been developed in parallel and that tap into the domain of job quality, such as quality of working life, decent work, employment quality, and quality of work [9][10][11][12][13][14][15][16][17]. To make things even more complicated, authors (from different disciplines) referring to the same concept often mean different things (e.g., employment quality [10,13]) and some authors seem to use a few terms interchangeably [12,14,15].…”
Section: Definition and Conceptualization Of Job Quality Quality Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The worker invests many hours of the day in a work space in which physical and social conditions converge to which he arrives with his particularities and personal aspirations that he must manage to achieve an efficient execution of his work and a balance between his work life and the external world. The quality of life at work is associated with objective characteristics of the work and the subjective evaluation that the person makes of them (Steffgen, Khol, Reese, Happ, & Sischka, 2015). The emphasis of the meaning of the construct is the worker's assessment of his work life, in the subjective, individual psychological experience and satisfaction (Lehman, 1988) and, it is important because it can support or not to health, safety and a better balance between the employee's personal and work life (Eurofond, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the importance of quality of life at work has been recognized for its influence on physical and mental health, job satisfaction, well-being and work-family balance of the employee and multiple investigations (eg Beham & Drobonic, 2010;Bobé, Trobat, Sampietro, 2008;Dahl, Nesheim & Olsen, 2009; Eurofond, 2016a and b; Eurfond, 2017; Greenhaus, Collin, & Shaw, 2003;Steffgen et al, 2015;Wallace et al, 2007). However, specific studies on janitor employees are scarce in the international context and in Mexico they almost do not exist.…”
Section: Introductionmentioning
confidence: 99%